Avaliação do Programa de Erradicação do Trabalho Infantil em Mossoró-RN - Morais, Fernanda Kallyne Rêgo de Oliveira (2008)
This research aims to evaluate the Elimination of Child Labor Program – PETI in Mossoró-RN related to life style changes in families that have kids and teenagers trated by the program. Documentary and fields researches were made, the last one happened between march and August 2009. A questionary was given to the people responsible to the children and teenagers, who have been treated by the program for four years or longer, in two different steps. The quantitative information was submitted to a descriptive treatment, using absolut and relative frequency, simple tables, crossings, reference indicators andspecific tests. The quantitavie information was privided by the analisys of speech method and analysed taken into account the rules of the authors who discuss and theorize childlabor and its different sides. From all the 30 families that were interviewed in the first sample, most of the people that are responsible for the children and teenagers are young women, that live with their kids and husband, and have low education. Since tha registration in the PETI program until the date that this research was made, the percentage of employment and kids in school. Also in 33,4% of the families there were kids or teenagers working. The monthly income and expenditure with food, rent, kitchen gas, eletric power and house loan; more families purchased their own houses , less ones had to pay rent or borrowed houses,increased the numbers of masonry houses and their rooms; the number of appliances such as refrigerators, blenders, television sets, stereo systems, telephones, sewing machines,bicycles and radios. Most of the responsible for the children also worked when they were younger,come from large families, from the rural zone and appreciate things like honesty and integrity. They had nice memories about toys and plays between siblings, though there was an ambivalence related to their working during their childhood and about the bossy way that they were raised. They are aware that nowadays is more difficult to raise children comparing to when they were younger and they find positive the fact that they are in the program, even though we found a few misconception about that. Plans for the future are simple and care to having their kids studying and having a good job when they get older. The early employment lasted for three generation.We may conclude that families improved their life styles,with positive changes in the families profiles after applying to the PETI program and also that poverty is still strong. The inconsistencies found indicate the program managers in town need to look carefully and develop projects to help the families that still go through child labor and also to have those families more sociable.Besides all that, later on, it is important to go deeper in the evaluation of the program when related to some aspects.